Application of in vitro Drug Metabolism Studies in Chemical Structure Optimization for the Treatment of Fibrodysplasia Ossificans Progressiva (FOP) - Padilha, Elias C. [UNESP]; Wang, Jianyao; Kerns, Ed; Lee, Arthur; Huang, Wenwei; Jiang, Jian-kang; McKew, John; Mutlib, Abdul; Peccinini, Rosangela G. [UNESP]; Yu, Paul B.; Sanderson, Philip; Xu, Xin (Frontiers Media Sa, 2019)
Currently no approved treatment exists for fibrodysplasia ossificans progressiva (FOP) patients, and disease progression results in severe restriction of joint function and premature mortality. LDN-193189 has been demonstrated to be efficacious in a mouse FOP disease model after oral administration. To support species selection for drug safety evaluation and to guide structure optimization for back-up compounds, in vitro metabolism of LDN-193189 was investigated in liver microsome and cytosol fractions of mouse, rat, dog, rabbit, monkey and human. Metabolism studies included analysis of reactive intermediate formation using glutathione and potassium cyanide (KCN) and analysis of non-P450 mediated metabolites in cytosol fractions of various species. Metabolite profiles and metabolic soft spots of LDN-193189 were elucidated using LC/UV and mass spectral techniques. The in vitro metabolism of LDN-193189 was significantly dependent on aldehyde oxidase, with formation of the major NIH-Q55 metabolite. The piperazinyl moiety of LDN-193189 was liable to NADPH-dependent metabolism which generated reactive iminium intermediates, as confirmed through KCN trapping experiments, and aniline metabolites (M337 and M380), which brought up potential drug safety concerns. Subsequently, strategies were employed to avoid metabolic liabilities leading to the synthesis of Compounds 1, 2, and 3. This study demonstrated the importance of metabolite identification for the discovery of novel and safe drug candidates for the treatment of FOP and helped medicinal chemists steer away from potential metabolic liabilities.
Keywords: metabolite identification; fibrodysplasia ossificans progressiva; structure optimization; aldehyde oxidase; reactive metabolite